SAPROLEGNIASIS OF BARBUS SHARPEYI , GUNTHER (BUNNEI FISH) IN BASRAH / IRAQ - AL-DUBOON, A.H.; Al-Mukhtar, M. A.; JASSIM, A.A.R.; BADER, S.Q.; AL-ZAWAR, J.M. (Iraqi Journal of Aquaculture, 2022)
Among 600 bunnei fishes transferred from Qurna marshes to fish ponds at Basrah University/Marine Science Center, 211 fishes were infected with saprolegniasis during the period from January to March, 2005 constituting a percentage of infection of 35.1% which was diagnosed by its clinical features and by direct examination with 10% KOH solution and by culture. The cultutred fungus was Saprolegnia parasitica.